The temporal relationships between sleep disturbance and autonomic dysregulation: A co-twin control study. (1st September 2022) - Huang, Minxuan; Bliwise, Donald L.; Shah, Amit; Johnson, Dayna A.; Clifford, Gari D.; Hall, Martica H.; Krafty, Robert T.; Goldberg, Jack; Sloan, Richard; Ko, Yi-An; Da Poian, Giulia; Perez-Alday, Erick A.; et al.
Abstract: Introduction: Sleep disturbance is associated with autonomic dysregulation, but the temporal directionality of this relationship remains uncertain. The objective of this study was to evaluate the temporal relationships between objectively measured sleep disturbance and daytime or nighttime autonomic dysregulation in a co-twin control study. Methods: A total of 68 members (34 pairs) of the Vietnam Era Twin Registry were studied. Twins underwent 7-day in-home actigraphy to derive objective measures of sleep disturbance. Autonomic function indexed by heart rate variability (HRV) was obtained using 7-day ECG monitoring with a wearable patch. Multivariable vector autoregressive models with Granger causality tests were used to examine the temporal directionality of the association between daytime and nighttime HRV and sleep metrics, within twin pairs, using 7-day collected ECG data. Results: Twins were all male, mostly white (96%), with mean (SD) age of 69 (2) years. Higher daytime HRV across multiple domains was bidirectionally associated with longer total sleep time and lower wake after sleep onset; these temporal dynamics were extended to a window of 48 h. In contrast, there was no association between nighttime HRV and sleep measures in subsequent nights, or between sleep measures from previous nights and subsequent nighttime HRV. Conclusions: Daytime, but not nighttime, autonomic function indexed by HRV has bidirectional associations with several sleep dimensions. Dysfunctions in autonomic regulation during wakefulness can lead to subsequent shorter sleep duration and worse sleep continuity, and vice versa, and their influence on each other may extend beyond 24 h. Highlights: Autonomic function and sleep are closely inter-related. Daytime rather than nighttime autonomic function has bidirectional associations with sleep quality measures. The temporal dynamics of the association may extend beyond a 24-h period.